Prevalence of various risk factors associated with new-onset epilepsy after the age of 50: a retrospective population-based study - Cvetkovska, Emilija; Babunovska, Marija; Boskovski, Bojan; Kuzmanovski, I; Tanovska, Nikolina; Kiteva Trenchevska, Gordana (Wiley, 2022)
Population-based studies of epilepsy risk factors are rare. We aimed to evaluate the prevalence of various risk factors associated with new-onset epilepsy after the age of 50 years. We included all incident cases in North Macedonia between 2015 and 2018. Study participants were ascertained from the national healthcare platform. We performed a retrospective analysis of Electronic Health Records of 2,367 patients (1,017 females and 1,350 males) whose epileptic seizures started after the age of 50 years. Patients were stratified into 10-year age groups. The most common risk factor for new-onset epilepsy in our cohort was stroke, which was associated with new-onset epilepsy in 20% of patients aged 50-59 years and almost 50% of patients aged 70-79 years. The second most frequent risk factor was neoplasm in patients aged 50-69 years and dementia in patients older than 70 years. The other pre-existing conditions included: metabolic disorders, traumatic brain injury, and postencephalitic and inflammatory diseases. Chronic alcoholism was the most common metabolic risk factor associated with new-onset epilepsy and accounted for 84% of cases in this subgroup. Only metabolic disorders were significantly more frequent in males than in females (p<0.00001). We did not identify any epilepsy risk factor in 967 patients (41%). Systemic vascular risk factors were frequent in our cohort: 1,574 patients had hypertension (66%) and 449 patients had diabetes (19%), and 339 had both conditions (14%). We found that structural lesions were the most prevalent risk factor associated with new-onset epilepsy in middle-aged and elderly patients. Recognition of possibly modifiable factors associated with late-onset epilepsy could have a positive impact on reducing the risk of developing epilepsy.